A Framework Of Big Data As Service Platform For Access Control & Privacy Protection Using Blockchain Network - et. al., Santosh Kumar Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Big Data As A Service Is Used In Today’s Scenario To Handle And Process The Big Amount Of Data Which Are Generated From Different Source Every Day. Since Data Is Stored On The Cloud Platform, The System Could Suffer A Failure And Give Attackers The Opportunity To Launch Various Categories Of Attacks.Manyresearcheshave Been Done In This Domain To Provide Security And Protection To The Data On Cloud. The Blockchain Technology Is A Secure, Distributed And Privacy-Preserving Decentralized Ledger Where The Transactions Are Flexible, Secure,Verifiable And Permanent Way.Here, The Transaction Data Is Encrypted Andkept In A Wrapped Block (I.E., Record) Which Are Spreadthrough The N/W In A Provable And Unabashedmode Across The Entire Network To Enhance Information Security And Data Privacy. In This Paperwe Have Proposed A Framework For An Access Control With Privacy Protection In Bdaas Based On Blockchain Technology. Here Blockchain Technology Is Used Only For Storing The Transaction Log Information Whenever Any Kind Of Event Log Occurred In System.